Intracellular expression of toll-like receptor 4 in neuroblastoma cells and their unresponsiveness to lipopolysaccharide - Mori Isamu; Koide Naoki; Naiki Yoshikazu; Tumurkhuu Gantsetseg; Islam Shamima; Hassan Ferdaus; Yoshida Tomoaki; Yokochi Takashi (BMC Cancer, 2006)
Abstract Background Recently it has been reported that, toll-like receptors (TLRs) are expressed on a series of tumor cells, such as colon cancer, breast cancer, prostate cancer, melanoma and lung cancer. Although some cancer cells like melanoma cells are known to respond to lipopolysaccharide (LPS) via TLR4, not all cancer cells are positive for TLR4. There is little information on the expression and function of TLR4 in neuroblastoma cells. In this study, we investigated the expression of TLR4 in human neuroblastoma NB-1 cell line. Methods Expression and localization of TLR4 were detected by reverse transcription-polymerase chain reaction (RT-PCR) and flow cytometric analysis, respectively. Activation of nuclear factor (NF)-κB by LPS was detected by degradation of IκB-α and NF-κB luciferase assay. Activation and expression of mitogen-activated protein (MAP) kinase and interferon regulatory factor (IRF)-3 was detected by immunoblot analysis. Results Human NB-1 neuroblastoma cells expressed intracellular form of TLR4, but not the cell surface form. Further, NB-1 cells express CD14, MD2 and MyD88, which are required for LPS response. However, LPS did not significantly induce NF-κB activation in NB-1 cells although it slightly degraded IκB-α. NB-1 cells expressed no IRF-3, which plays a pivotal role on the MyD88-independent pathway of LPS signaling. Collectively, NB-1 cells are capable to avoid their response to LPS. Conclusion Although human NB-1 neuroblastoma cells possessed all the molecules required for LPS response, they did not respond to LPS. It might be responsible for intracellular expression of TLR4 or lack of IRF-3.